KAJIAN WAKTU STRANGULASI TERHADAP PEMBUNGAAN JERUK PAMELO ‘CIKONENG’ (Citrus grandis (L.) Osbeck) - Muhammad Thamrin (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2009)
An Assessment Time of Strangulation on Flowering Induction of Pummelo ‘Cikoneng’ (Citrus grandis (L.) Osbeck). Field assessment was conducted at Farmer’s Field Bantarmara Village, Cisarua, Sumedang region, West Java from August 2007 to May 2008, to determine the effect of different strangulation times on flowering induction of Pummelo during flowering-off season. Three strangulation times (1,2 and 3 months after harvest, MAH) were arranged in randomized complete block design with 6 (six) replications. An assessment results showed that strangulation at 3 MAH effectively induced flowering appearance (83%) and increased numbers of generative shoots, flowering cluster, bud, blooming, fruit formation and fruit setting. On the other hand, all treated plants had higher C/N ration than control. Kajian lapang dilaksanakan di Tanah Petani (TP) Bantarmara, kecamatan Cisarua, kabupaten Sumedang, Jawa Barat dari bulan Agustus 2007 sampai Mei 2008, untuk melihat waktu strangulasi yang tepat untuk menginduksi bunga diluar musim. Tiga waktu strangulasi (1, 2 dan 3 bulan setelah panen, BSP) disusun menurut rancangan acak kelompok dan 6 (enam) ulangan. Hasil kajian menunjukkan bahwa waktu strangulasi 3 BSP cukup efektif menginduksi jumlah muncul bunga (83%), tetapi mempengaruhi jumlah tunas generative, kluster bunga, kuncup bunga, bunga mekar, buah terbentuk dan fruit set masing-masing 32,67; 28,17; 220,00; 143.33; 61,17 dan 39,02%. Di samping itu, rasio C/N daun pada semua perlakuan lebih tinggi dari control.